High throughput screening of photocatalytic conversion of pharmaceutical contaminants in water. (January 2017) - Romão, Joana; Barata, David; Ribeiro, Nelson; Habibovic, Pamela; Fernandes, Hugo; Mul, Guido
Abstract: The susceptibility for photon-induced degradation of over 800 pharmaceutical compounds present in the LOPAC 1280 library, was analyzed by UV/Vis spectroscopy in the absence or presence of TiO2 P25 in water. In general, few compounds were effectively degraded in the absence of the TiO2 photocatalyst (3% of all compounds tested), while in the presence of TiO2, the majority of compounds was converted, often to a large degree. Differences in degree of degradation are evaluated on the basis of molecular weight, as well as the chemical nature of the drug compounds (functional groups and pharmacological classes). In general, if the molecular weight increases, the degradation efficacy decreases. Relatively high degrees of conversion can be achieved for (relatively small) molecules with functional groups such as aldehydes, alcohols, ketones and nitriles. A low degree of conversion was observed for compounds composed of conjugated aromatic systems. Trends in degradation efficacy on the basis of pharmacological class, e.g. comparing hormones and opioids, are not obvious. Graphical abstract: Highlights: Photocatalysis is effective for conversion of many pharmaceutical contaminants in water. Rate of conversion correlates with molecular weight. Functionalities such as aldehyde, alcohol, ketone and amide, promote rate of conversion. Conjugated aromatic systems (adenosine, caffeine, imidazole) show low reactivity. Abstract : This manuscript describes the largest data set on susceptibility of aqueous phase pharmaceutical compounds towards TiO2 induced photocatalytic conversion on record.